Exceptional Women and Classical Borrowings : A Case Study of Margaret Cavendish's Use of Latin and Greek Loanwords - Knuuttila, Rasmus (My University, 2025)
This study examines Margaret Cavendish’s use of Latin and Greek loanwords in five of her texts, published between 1655 and 1671. The examined texts cover a number of different genres, including, among others, a play, two letter collections and an essay collection. Previous historical sociolinguistic research into women’s lexical usage in the Early Modern period is very scarce. The aim of this study is to contribute to filling this gap. The study is quantitative in nature. It examines the frequencies and the relative frequencies of 26 lexemes in Cavendish’s texts. 16 lexemes are of Latin origin and 10 lexemes are of Greek origin. The results from Cavendish’s texts are compared with the more male-dominated Early English Books Online (EEBO) corpus. Overall, the results from Cavendish’s texts follow the same trends that can be observed in the EEBO- corpus, although some trends appear more clearly than others. Of the examined Latin loanwords, seven occur in Cavendish’s texts. The only one of the examined Greek loanwords to occur is alphabet. The results of this study tentatively suggest that previous research has too categorically assumed that women were behind men in borrowing in the Early Modern English period. However, much more future research is required to confirm the conclusions drawn in this thesis. On a more methodological level, this study concludes that the different genres and types of texts selected for this kind of research can also have a marked effect on the occurrences of individual lexemes in the dataset. This is something that future studies should also take into account.
Keywords: Loanwords, Historical Sociolinguistics